2021
DOI: 10.1038/s41435-021-00126-8
|View full text |Cite
|
Sign up to set email alerts
|

The aging gut microbiome and its impact on host immunity

Abstract: The microbiome plays a fundamental role in the maturation, function, and regulation of the host-immune system from birth to old age. In return, the immune system has co-evolved a mutualistic relationship with trillions of beneficial microbes residing our bodies while mounting efficient responses to fight invading pathogens. As we age, both the immune system and the gut microbiome undergo significant changes in composition and function that correlate with increased susceptibility to infectious diseases and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
167
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(173 citation statements)
references
References 145 publications
6
167
0
Order By: Relevance
“…During aging, the gut microbiota composition decreases in diversity and stability (42). It has been postulated that these changes may evoke hyperstimulation of the immune system resulting in persistent, low-grade inflammation (43), referred to as "inflammaging" (4), a phenomenon observed in the elderly. In addition, decreased immune function, or 'immunosenescence', is a hallmark of aging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During aging, the gut microbiota composition decreases in diversity and stability (42). It has been postulated that these changes may evoke hyperstimulation of the immune system resulting in persistent, low-grade inflammation (43), referred to as "inflammaging" (4), a phenomenon observed in the elderly. In addition, decreased immune function, or 'immunosenescence', is a hallmark of aging.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, decreased immune function, or 'immunosenescence', is a hallmark of aging. Both inflammaging and immunosenescence contribute to aging of the peripheral immune system, which is associated with higher susceptibility to infection, increased risk of autoimmune diseases and impaired cognitive function (4,43).…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that there was a significant difference in the mean age between PA patients and primary hypertension patients. Several studies have revealed that age is a factor influencing the gut microbiota (41)(42)(43)(44). As people age, key changes in gut microbiota include compositional instability, reduced overall diversity, and an increase in proinflammatory opportunistic pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al 2019). The recent comprehensive studies on the effect of ageing on the gut microbiome and its impact on host immunity, microbiome composition and distribution could be found in other reviews too (Buford 2017;Nagpal et al 2018;Bosco and Noti 2021). Metabolomic study on microbiota by David Rojo suggested its implication in various physiopathology associated with human such as inflammation, oxidative stress and gut permeability (Konjevod et al 2021).…”
Section: Immunoregulatory Microbesmentioning
confidence: 99%